Digital Human Modeling: Applications in Health, Safety, Ergonomics and Risk Management: Human Modeling 6th International Conference, DHM 2015, Held as Part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings, Part I - Duffy, Vincent G. (Information Systems and Applications, incl. Internet/Web, and HCI, 2015)
The two-volume set LNCS 9184-9185 constitutes the constitutes the refereed proceedings of the 6th International Conference on Digital Human Modeling and Applications in Health, Safety, Ergonomics and Risk Management 2015, held as part of the 17th International Conference on Human-Computer Interaction, HCII 2015, held in Los Angeles, CA, USA, in August 2015. The total of 1462 papers and 246 posters presented at the HCII 2015 conferences was carefully reviewed and selected from 4843 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers thoroughly cover the entire field of human-computer interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The total of 96 contributions included in the DHM proceedings were carefully reviewed and selected for inclusion in this two-volume set. The 44 papers included in this volume are organized in the following topical sections: modeling human skills and expertise; modeling human work and activities.